The association between nutritional status measured by body mass index and outcomes in the pediatric intensive care unit - Pournasiri, Zahra; Bakhtiary, Mahsa; Nikparast, Ali; Hashemi, Seyedeh Masumeh; Narjes Ahmadizadeh, Seyyedeh; Behzad, Azita; Asghari, Golaleh (Frontiers in Pediatrics, 2024)
Aim/Introduction: The relationship between nutritional status upon admission to a pediatric intensive care unit (PICU) and clinical outcomes remains unclear. We examined the relationship between nutrition status, as indicated by body mass index-for-age (BMI-for-age), and clinical outcomes in the PICU. Method: In this retrospective study at a tertiary care center, records of 1015 critically ill children and adolescents aged one month to 18 years old with available anthropometric parameters were included. The nutritional status upon admission was determined by calculating the BMI-for-age z-score using the WHO growth charts as the reference. The participants were categorized as underweight (BMI-for-age z-score<-2), normal weight (-2≤BMI-for-age z-score≤+1), and overweight/obese (BMI-for-age z-score>+1). Multi-variate odds ratios (OR) with 95% confidence intervals (CI) were used to investigate the association between malnutrition (being underweight and overweight/obese) and odds of Prolonged PICU stay (≥7d) and PICU mortality after controlling for descriptive characteristics, Glasgow Coma Scale score status, fluctuations in serum sodium, and acute kidney injury confounders. Results: The proportions of patients in underweight, normal weight, and overweight/obese categories were 34.2%, 45.8%, and 20%, respectively. During the study period, 21.5% of patients had prolonged PICU stay, and 5.6% of patients in PICU died. Compared to normal-weight patients, underweight patients had higher odds of prolonged PICU stay (OR:1.52;95%CI:1.05-2.22) and PICU mortality (OR:2.12;95%CI:1.22-4.01). Age- and gender-stratified full-adjusted analysis showed that the increased odds of prolonged PICU stay remained significant among underweight boys and underweight individuals aged 5-19 years old. Furthermore, the increased odds of PICU mortality remained significant among underweight individuals aged 2-5 years old. However, being overweight or obese during PICU admission did not demonstrate a significant association with our outcomes in the total sample or subgroup analysis. Conclusion: Our findings showed that PICU patients who were underweight had higher odds of prolonged PICU stay and PICU mortality than their normal-weight counterparts. This underscores the importance of closely monitoring underweight patients in the PICU upon admission in order to improve clinical outcomes.